OTONOMI DAERAH DAN PERMINTAAN TABUNGAN MASYARAKAT STUDI KASUS EMPAT PROPINSI DI PULAU JAWA - Supripto, Supripto (Jurnal Analisis Bisnis Ekonomi, 2008)
This research investigated demand of Deposits. Data used was panel data, which is combination from time series data and cross sectional data. Estimation method used was generalized least square (GLS) with polled regression and fixed effect (Covariance model). Based on restricted F test and Lagrance Multiplier test (LM test), it is known taht fixed effect model is the best model to explain demand for of deposit. It menas taht element of region (provincy) effects model structure. Least Square Dummy Variable (LSDV) regression model by incorporating time element indicates that local autonomy event influence model structure, that the model is not stable due to enforcement of Law No 22 and 25 of 1999.